(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article provides detailed information on the science and tasks of osteology, anatomy, anthropology and paleontology, skeletal elements, morphology of microbones, ossification process, long tubular bones, hollow bones, flat bones, and immobile and mobile joints.